Associations of co-exposure to polycyclic aromatic hydrocarbons and vitamin D with early lung dysfunction: Mediating roles of metabolic score-visceral adiposity index - Baihao Lin; Wanlu Liu; Hank-Han Wang; Haixia Qian; Xinyu Zhu; Mengya Xu; Yuyu Zheng; Nada Alhazmi; Yansen Bai (Ecotoxicology and Environmental Safety)
Background: Preserved ratio impaired spirometry (PRISm) and airflow obstruction are recognized as critical early signs of chronic obstructive pulmonary disease (COPD). While these conditions arise from concurrent exposure to toxicants and essential nutrients, how vitamin D modifies the pulmonary toxicity induced by polycyclic aromatic hydrocarbons (PAHs) and the metabolic mechanisms involved is still unclear. Methods: Based on the National Health and Nutrition Examination Survey (NHANES) 2007–2012, data on urinary PAH metabolites (ΣOH-PAHs), serum vitamin D metabolite levels [Σ25(OH)D], and pulmonary function tests [forced expiratory volume in one second (FEV1), forced vital capacity (FVC) and FEV1/FVC] from 2189 participants, including 369 subjects with early lung dysfunction, defined as PRISm or airflow obstruction. Multiple metabolic disorder indicators were calculated using biochemical markers. The interaction effects between vitamin D and PAHs were evaluated using multiple linear and logistic regression models. Causal mediation analyses and structural equation modeling were employed to investigate the mediating roles of metabolic indicators. Results: PAHs and vitamin D had opposite effects on lung function parameters [FEV1: β (95 CIs) = -0.01 (-0.02, −0.01) vs. 0.01 (0.01, 0.04); FVC: β (95 CIs) = -0.01 (-0.02, 0.01) vs. 0.04 (0.01, 0.06)] and risk of early lung dysfunction [OR (95 CIs) = 1.22 (1.06, 1.40) vs. 0.52 (0.37, 0.73)]. Decreased associations of ΣOH-PAHs with FEV1, FVC, and early lung dysfunction, as well as with metabolic score-visceral adiposity index (MSV) were visualized with increased Σ25(OH)D among subjects with body mass index (BMI) < 28 kg/m2. Furthermore, 2.18 %, 18.20 %, 5.70 %, and 4.70 % of the associations of co-exposure to ΣOH-PAHs and Σ25(OH)D with FEV1, FVC, FEV1/FVC, and early lung dysfunction disease were mediated by MSV. Conclusions: Our findings indicated that vitamin D antagonizes the hazardous effects of PAHs on early lung dysfunction by metabolic alteration, providing new insight into the identification of the underlying high-risk populations and accessible prevention and intervention measures for attenuating PAH-induced lung dysfunction.